Church of Wisdom in Baghdad in 1929 Historical study (Journal of the College of Education for Women, 2019)
The study highlights the rivalry of foreign interests in Iraq, especially after the establishment of the monarchy in 1921. This period was characterized by extensive American activity in Iraq in general and Baghdad in particular. This activity increased after the Americans obtained the concession which came in the light of Article IV of the 1930 Treaty. Which officially guaranteed US interests in Iraq. The research also discussed the efforts of the Jesuit Fathers in Baghdad to convert the Church of Wisdom from a place of worship and rites of the Christian religion to a school of the propagation of science and culture along the lines of American schools, College Baghdad), which has become an important school in Baghd